2000
DOI: 10.1128/jb.182.10.2823-2830.2000
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of the Mechanisms for Oxidation of Cytosolic NADH by Saccharomyces cerevisiae Mitochondria

Abstract: During respiratory glucose dissimilation, eukaryotes produce cytosolic NADH via glycolysis. This NADH has to be reoxidized outside the mitochondria, because the mitochondrial inner membrane is impermeable to NADH. In Saccharomyces cerevisiae, this may involve external NADH dehydrogenases (Nde1p or Nde2p) and/or a glycerol-3-phosphate shuttle consisting of soluble (Gpd1p or Gpd2p) and membrane-bound (Gut2p) glycerol-3-phosphate dehydrogenases. This study addresses the physiological relevance of these mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
151
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(157 citation statements)
references
References 39 publications
5
151
1
Order By: Relevance
“…Deletion of HAP4 deprives the cells of its excess respiratory capacity, and hence there is ethanol formation at lower glycolytic fluxes. In agreement with our hypothesis, deletion of both NDE1 and NDE2 (external mitochondrial NADH dehydrogenases encoded by NDE1 and NDE2, which oxidize cytosolic NADH and couple it to the respiratory chain) reduced the D crit only by 23% (34,35), which is in sharp contrast to 75% reduction for the hap4⌬ mutant observed here. dos Santos et al (36) reported that overexpression of malic enzyme leads to a decrease in the critical dilution rate by as much as 54% of the WT.…”
contrasting
confidence: 53%
“…Deletion of HAP4 deprives the cells of its excess respiratory capacity, and hence there is ethanol formation at lower glycolytic fluxes. In agreement with our hypothesis, deletion of both NDE1 and NDE2 (external mitochondrial NADH dehydrogenases encoded by NDE1 and NDE2, which oxidize cytosolic NADH and couple it to the respiratory chain) reduced the D crit only by 23% (34,35), which is in sharp contrast to 75% reduction for the hap4⌬ mutant observed here. dos Santos et al (36) reported that overexpression of malic enzyme leads to a decrease in the critical dilution rate by as much as 54% of the WT.…”
contrasting
confidence: 53%
“…As expected, the LEU2 gene showed only background expression, while genes coding for branched-chain amino acid aminotransferases, i.e., BAT1 and BAT2, showed inverse expression correlating with the cells transitioning from logarithmic to growth-arrested phase (10). It is therefore likely that the improved growth of the SPT15-300 mutant under leucine-limiting conditions is due to increased uptake and utilization of leucine (9,28,36).…”
Section: Resultsmentioning
confidence: 89%
“…These proteins include Ald4p, Ald6p and Gpp1p. Other possible redox shuttles in addition to the Adh3p-catalyzed ethanol-acetaldehyde shuttle are glycerol-3-phosphate shuttle, malate-oxaloacetate shuttle and malate-aspartate shuttle (Bakker et al, 2001;Barron et al, 1998;Overkamp et al, 2000). The shuttling of NADH from cytosol could be a major contributor also for the observed decrease in the activity of the TCA-cycle.…”
Section: Effects Of Cofactor Imbalance At the Pyruvate Branchpoint Anmentioning
confidence: 99%